DEALING WITH HETEROGENEOUS GROUPS: PROBLEMS AND SOLUTIONS (American Journal of Pedagogical and Educational Research, 2023)
An analysis of the needs of representatives of heterogeneous groups of students is presented. Particular attention is paid to the needs of three categories of students – gifted, socially disadvantaged, and with disabilities. Recommendations are given for the development of vocational training and retraining programs.